Contextual Factors Influencing the MAMAACT Intervention: A Qualitative Study of Non-Western Immigrant Women’s Response to Potential Pregnancy Complications in Everyday Life - Johnsen, Helle (Int J Environ Res Public Health, 2020)
In western countries, immigrant women have an increased risk of negative birth outcomes. Immigrant women’s and maternity care system’s delayed response to pregnancy complications contribute to ethnic inequities in reproductive health. The MAMAACT intervention was developed to improve midwives’ and women’s response to pregnancy complications in Denmark. The study examines the context of the implementation of the MAMAACT intervention and investigates how the intended intervention mechanisms regarding response to pregnancy complications were affected by barriers in non-Western immigrant women’s everyday life situations. Twenty-one interviews with non-Western immigrant women were undertaken. Systematic text condensation and the situational-adaptation framework by Alonzo were used to analyze data. Four main categories were identified: ‘Sources of knowledge during pregnancy’, ‘Containment of pregnancy warning signs’, ‘Barriers during the onset of acute illness’ and ‘Previous situations with maternity care providers’. Attention to potential pregnancy complications may conflict with immigrant women’s everyday life situations and result in the containment of symptoms as well as causing delays in seeking medical assistance. It is probable that barriers in women’s everyday life will impact the intended intervention mechanisms and thus the full potential of the intervention may not be reached.